The Effect of Point Illustration Explanation Toward Student writing skill in Writing Descriptive Text at second Grade Student of SMA Negeri 1 Lenek - Tawali (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
This research aimed to find out the effect of Point Illustration Explanation students’ writing skill in descriptive text at second grade student of SMA Negeri Lenek in academic year 2022/2023. The subject of this study were 66 students. The method of this research was quantitative method quasi- experimentals study with nonequivalent control group design. The technique of data collection applied in this study was written test. Then the procedure of data analysis in this study was descriptive analysis statistical, by finding out the mean score, the median score, mode, standard deviation and inferential analysis is to find out the t-test then examine by t-table to know whether the point illustration explanation as the strategy to use in teaching writing skill focused on descriptive text is significant in this research this analysis used the theory of Arikunto 2014. The result of this research, the researcher found out that t-test was 5,92 the level of (005) 95 % then t-table was 200, the degree of freedom 64. Based on the result t-test can be concluded that by Applying Point Illustration Explanation was significance in writing skill for descriptive text.